2023
DOI: 10.1186/s12872-023-03319-3
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin derived amyloid deposits in the atrium and the aortic valve: insights from multimodality evaluations and mid-term follow up

Abstract: Background Recent studies have reported atrial involvement and coexistence of aortic stenosis in transthyretin (ATTR) cardiac amyloidosis (CA). However, pathological reports of extraventricular ATTR amyloid deposits in atrial structures or heart valves are limited, and the clinical implications of ATTR amyloid deposits outside the ventricles are not fully elucidated. Case presentation We report 3 cases of extraventricular ATTR amyloid deposits conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…In recent years, the evaluation of ATTR deposition in the atria has been given increased attention [8][9][10][11]. We previously found that ATTR deposition patterns within the atrial septum (AS) differed on each side [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the evaluation of ATTR deposition in the atria has been given increased attention [8][9][10][11]. We previously found that ATTR deposition patterns within the atrial septum (AS) differed on each side [12].…”
Section: Introductionmentioning
confidence: 99%
“…2 factor-derived amyloid (AANF) is commonly found in the atria of nearly all old-aged patients with a left-predominant deposition [13][14][15], the deposition pattern of ATTR in the left and right atrial regions remain uninvestigated. Furthermore, several studies have reported the potential colocalisation of ATTR and AANF [8,11,12,16]. However, the relationship between ATTR and AANF is yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%